Effect of Exchange Rate, Foreign Direct Investment and Portfolio Investment on the Indonesian Economy: A Structural Cointegrating Vector Autoregression Approach - Arintoko, Arintoko; Insukindro, Insukindro (International Journal of Economics and Financial Issues, 2017)
This study develops macroeconomic models that involves the output gap, the level of prices, interest rates, exchange rates, current account, foreign direct investment and portfolio investment. The modeling adapts to the characteristics of the data, the perspective of a new macroeconomic theories that are relevant to the conditions in Indonesia, and the appropriate methodology used structural cointegrating vector autoregression (SCVAR). The test results indicate the presence of four significant cointegrations and affect change in macroeconomic variables that are endogenous. The four cointegrations are output gap, price, interest rates and exchange rates cointegration. The long-term relationships indicate that exchange rates cointegrated against the output gap, price, interest rate on the one hand and cointegrated by the interest rate, current account and foreign direct investment on the other. The exchange rate has a relationship with key macroeconomic variables in Indonesia. Taking into account the increasing globalization of economic and financial, policy of inflation targeting in Indonesia should be consistent in giving more attention to exchange rates and financial markets. Keywords: long-term relationships, structural cointegrating vector autoregression, inflation targeting JEL Classifications: C51, E10, E58, E66